Loka Pengawas Obat dan Makanan: Transformasi New Public Service dalam Reformasi Administrasi BPOM (Administratio, 2021)
Since the implementation of regional autonomy in 1999, the health sector has become a government affair carried out by the regions. Thus, the Ministry of Health no longer has a Regional Office like the Ministry of Finance or the Ministry of Religion. However, as a follow-up to regional autonomy, President Abdurrahman Wahid issued a Presidential Decree on Non-Departmental Government Institutions, which, regulates the establishment of the Badan Pengawas Obat dan Makanan (BPOM). BPOM functions as a central agency that has regional apparatus. In 2018, BPOM carried out administrative reforms by adding 40 new Echelon IV-level units in Loka Pengawas Obat dan Makanan. This study portrays administrative reform from the New Public Service perspective using an evaluation of the business process change framework, namely civil servants, citizens, public institutions, and processes. Loka POM's presence through BPOM administrative reform shows several New Public Service values ​​in civil servants, citizens, public institutions, and processes. This transformation is also supported by several performance data that show the expansion of drug and food control scope, allowing citizens to feel protected from drugs and foods that pose health risks. It requires comprehensive tools to measure outcomes, especially for citizens' elements. Through those tools, BPOM can identify their roles for citizens accurately.